Investigator-initiated, open-label trial of ustekinumab for the treatment of moderate-to-severe palmoplantar psoriasis. (June 2013) - Au, Shiu-Chung; Goldminz, Ari M.; Kim, Noori; Dumont, Nicole; Michelon, Melissa; Volf, Eva; Hession, Meghan; Lizzul, Paul F.; Andrews, Israel D.; Kerensky, Todd; Wang, Andrew; Yaniv, Shimrat; et al.
Abstract Background: Palmoplantar psoriasis is a variant of psoriasis resistant to many forms of treatment. Methods: Twenty subjects with moderate-to-severe psoriasis of the palms and soles, 50% with pustules at baseline, were treated with ustekinumab at weeks 0, 4, and 16. All subjects had previously failed topical corticosteroids. Dosing was 45 mg subcutaneously for subjects weighing <100 kg and 90 mg for subjects weighing ≥100 kg. The primary endpoint was the percent of subjects achieving clinical clearance at week 16, defined as Palm–Sole Physician's Global Assessment ≤1. The study received Tufts Medical Center IRB approval. Results:After 16 weeks of treatment, 35% (7/20) of subjects achieved clinical clearance. Sixty percent (12/20) improved two or more points on the Palm–Sole Physician's Global Assessment scale. Sixty-seven percent (6/9) of those receiving the 90 mg ustekinumab dose achieved clinical clearance compared with nine percent (1/11) receiving 45 mg (p = 0.02). At 24 weeks, mean values showed 56% improvement in Dermatology Life Quality Index, and 34% improvement in pain Visual Analogue Scale score (all p < 0.05). Limitations: Assessment tools for palmoplantar psoriasis are not yet validated. Five subjects withdrew or were lost to follow-up. Conclusion: This study demonstrates that ustekinumab dosed at 90 mg is effective in controlling signs and symptoms of palmoplantar psoriasis.